Safety evaluation of the food enzyme catalase from porcine liver - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2022)
Abstract The food enzyme catalase (hydrogen‐peroxide:hydrogen‐peroxide oxidoreductase; EC 1.11.1.6) is obtained from porcine liver by Avances Bioquímicos Alimentación, S.L. (Spain). The food enzyme is intended to be used in cheese production for decomposition of hydrogen peroxide in brine. The manufacturing process involves the use of a solvent not permitted in the production of foods and food ingredients according to Directive 2009/32/EC. Consequently, the food enzyme does not comply with the existing requirements in the EU.